2008
DOI: 10.4049/jimmunol.180.9.6421
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Expression of the Fractalkine Receptor CX3CR1 on Circulating Monocytes as New Feature of Sepsis-Induced Immunosuppression

Abstract: Although it is known that septic shock rapidly induces immune dysfunctions, which contribute to the impaired clearance of microorganisms observed in patients, the mechanisms for this phenomenon remain incompletely understood. We recently observed, in a microarray study, an altered circulating leukocyte CX3CR1 mRNA expression associated with patients’ mortality. As monocytes play a central role in septic shock pathophysiology and express high levels of CX3CR1, we therefore further investigated the alteration of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
92
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 108 publications
(104 citation statements)
references
References 63 publications
9
92
0
1
Order By: Relevance
“…CX3CR1 mRNA is downregulated in PBMCs from MARV-exposed animals at the late stage of infection. Studies of patients succumbing to septic shock found that CX3CR1 downregulation at both the mRNA and protein levels was associated with poor prognosis and immune exhaustion (32,39). Our results suggest that this downregulation also occurs in Marburg virus infection and that CX3CR1 levels could be monitored in Marburg virus-infected patients as a prognostic marker.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…CX3CR1 mRNA is downregulated in PBMCs from MARV-exposed animals at the late stage of infection. Studies of patients succumbing to septic shock found that CX3CR1 downregulation at both the mRNA and protein levels was associated with poor prognosis and immune exhaustion (32,39). Our results suggest that this downregulation also occurs in Marburg virus infection and that CX3CR1 levels could be monitored in Marburg virus-infected patients as a prognostic marker.…”
Section: Discussionmentioning
confidence: 75%
“…Interestingly, transcripts of the fractalkine receptor CX3CR1 were upregulated early (day 1 through 5) during MARV infection and were significantly down-modulated during late-stage disease (Fig. 5C), a behavior similar to its downregulation in sepsis patients (32). Appearance of Th2-associated cytokines.…”
Section: Evidence Of An Early Innate Immune Response In Marv-infectedmentioning
confidence: 82%
“…The gene most highly expressed in survivors, relative to non-survivors, was that encoding the chemokine receptor CX3CR1 (fractalkine receptor). In a subsequent validation study, these same investigators provided further evidence supporting the novel concept that dysregulation of CX3CR1 in monocytes contributes to immune-paralysis in human sepsis [52]. These studies further demonstrate the potential to discover novel pathways through discovery-oriented expression profiling.…”
Section: Discovery Of Novel Targets and Pathwaysmentioning
confidence: 76%
“…Theoretically, any gene that is consistently differentially regulated between survivors and non-survivors in a microarray dataset may warrant further investigation as a potential outcome biomarker. For example, a microarray study by Pachot and colleagues [27,52] identified CX3CR1 (fractalkine receptor) as a potential outcome biomarker in sepsis. Similarly, Nowak and colleagues [53] have leveraged microarray data to identify chemokine (C-C motif) ligand 4 (CCL4) as an outcome biomarker in children with septic shock.…”
Section: Biomarker Discoverymentioning
confidence: 99%
“…Similarly, acute HIV infection has also been associated with a dramatic increase in IL-8 (CXCR1 ligand) in both plasma [52,53] and lymphoid tissues [54], also potentially driving the recruitment of CXCR1 1 lymphocytes to the sites of infection or inflamed tissues [55]. However, several studies have demonstrated that persistent expression of IL-8 or fractalkine results in the internalization and downregulation of CXCR1 [56,57] and CX 3 CR1 [58] in multiple inflammatory conditions. Thus, it is likely that elevated expression of these chemokine receptor ligands during HIV infection may result in the downregulation of their receptors on NK cells, in an effort to regulate cytolytic lymphocyte recruitment to tissues.…”
Section: Discussionmentioning
confidence: 99%